2009
DOI: 10.1007/s00439-009-0678-x
|View full text |Cite
|
Sign up to set email alerts
|

Non-synonymous GIGYF2 variants in Parkinson’s disease from two Asian populations

Abstract: Mutations in the GIGYF2 gene at the PARK11 locus have recently been reported in Parkinson's disease (PD). However, the pathogenicity of some of these mutations has been debated. We conducted a comprehensive genetic analysis of the entire GIGYF2 gene in a cohort of young onset and familial PD patients, followed up with screening of specific variants in a separate group of PD and healthy controls. A total of 850 study subjects [450 Parkinson's disease (PD) patients and 400 controls] from two Asian countries were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Variants within several of these genes or loci modify the risk to develop PD or parkinsonism, but this property is outside the scope of this review article. *Mutations in GRB10-interacting GYF protein 2 (GIGYF2, PARK11) were found in PD families in 2008 [134], but subsequent studies found mutations in controls or not cosegregating with the PD phenotype in families [135][136][137][138][139][140][141]. **Mutations in HtrA serine peptidase 2 (HTRA2, Omi/HtrA2, PARK13) were found in another German family [142], but mutations were subsequently also identified in healthy control subjects [143,144].…”
Section: Discussionmentioning
confidence: 99%
“…Variants within several of these genes or loci modify the risk to develop PD or parkinsonism, but this property is outside the scope of this review article. *Mutations in GRB10-interacting GYF protein 2 (GIGYF2, PARK11) were found in PD families in 2008 [134], but subsequent studies found mutations in controls or not cosegregating with the PD phenotype in families [135][136][137][138][139][140][141]. **Mutations in HtrA serine peptidase 2 (HTRA2, Omi/HtrA2, PARK13) were found in another German family [142], but mutations were subsequently also identified in healthy control subjects [143,144].…”
Section: Discussionmentioning
confidence: 99%
“…Bras et al, (2009) [25] found also the p.N457T variant in a Portuguese control individual. On their turn, Tan et al, (2009) [27] identified 4 different heterozygous mutations in GIGYF2 (p.A2G, p.K421R, p.I768V and p.H1304L) in 7 of 450 Asian patients with PD, and not in 400 controls. None of the mutations reported by Lautier et al, (2008) [22] were found in this study [27].…”
Section: Gigyf2 (Park11)mentioning
confidence: 99%
“…However, in recent months, at least 10 replication studies [6–15] including the latest one by Samaranch et al. [15] in this journal have provided conflicting data to cast considerable doubt on the causal role of GIGYF2 .…”
Section: Summary Of Gigyf2 Studies In Parkinson’s Disease (Pd)mentioning
confidence: 99%
“…However, in recent months, at least 10 replication studies [6][7][8][9][10][11][12][13][14][15] including the latest one by Samaranch et al [15] in this journal have provided conflicting data to cast considerable doubt on the causal role of GIGYF2. For the benefit of easy reference, we have collated the main findings of these replication studies in Table 1.…”
mentioning
confidence: 99%